Direct Percutaneous Intratumoral Bleomycin Injection for Palliative Treatment of Impending Quadriplegia - Duncan, Ian C. (AJNR Am J Neuroradiol, 2004)
Summary: We describe a case of midcervical angiosarcoma causing compression of the cervical spinal cord, producing rapidly progressive neurologic deficits. The tumor had recurred despite previous resection and was refractory to radiation and chemotherapy. Shrinkage of the tumor by percutaneous embolization was not considered feasible. A single direct percutaneous intratumoral injection of 15 U of bleomycin produced sufficient tumor shrinkage to relieve the pressure on the spinal cord and thereby reverse some of the neurologic deficits and give adequate palliation against recurrence of this problem for the remainder of the patient’s life. Direct percutaneous intratumoral injection of bleomycin may thus be considered for palliation when other treatment methods have failed to elicit a suitable clinical response.